STUDY OF THE IMPACT OF CRACK RESISTANCE PARAMETERS ON THE CRITICAL LOAD OF A SPECIMEN WITH A MODE I CRACK UNDER THREE-POINT BENDING IN THE FRAMEWORK OF THE COHESIVE ZONE MODEL - Bogdanov, V.L.; Selivanov, D.M. (Reports of the National Academy of Sciences of Ukraine, 2024)
In the presented study, a cohesive zone model is used to study the behavior of a specimen with a mode I edge crack under three-point bending. The cohesive zone includes an internal model characterized by a trapezoidal traction separation law. The parameter marking the beginning of the softening region of the law is investigated for its effect on the shape of the law. The contact interaction is examined using the penalty method in finite element analysis, and the effect of various cohesive zone parameters, such as cohesive strength and shape parameters, on the critical load is studied. It is found that an increase in cohesive strength leads to a decrease in cohesive length and an increase in crack mouth displacement. Moreover, it is observed that critical load predictions using nonlinear fracture mechanics agree more closely with linear fracture mechanics predictions as the cohesive strength increases. A similar effect is observed when the shape of the cohesion law approaches a uniform law. The study highlights the key role of cohesive zone parameters in influencing crack behavior and provides insights into their optimization to improve predictive modeling in fracture mechanics.